Advances in the Prevention of Cerebral Ischaemia Due to Atrial Fibrillation - A. Gil Núñez (Neurología (English Edition), 2010)
Introduction: Stroke and atrial fibrillation (AF) are a real vascular epidemic, and the consequences are disastrous. The most common complication of AF is stroke. Background: The correct aetiological diagnosis of stroke is essential for adequate prevention. The percentage of cryptogenic ischaemic strokes is far too high and the detection of AF needs to be improved. Cardio-embolic cerebral ischaemia due to AF is preventable, however due to medical inertia, the lack of compliance by the patient, and the problems with oral vitamin K antagonist anticoagulants, means that many patients with AF are at risk of suffering from a stroke. Conclusions: The significant recent advances with drugs such as dronedarone and dabigatran, provide real hope for an improvement in its prevention, and for this reason neurologists must know about them. Resumen: Introducción: El ictus y la fibrilación auricular (FA) son una verdadera epidemia vascular, y sus consecuencias son catastróficas. La complicación más común y devastadora de la FA es el ictus. Desarrollo: El diagnóstico etiológico correcto del ictus es esencial para poder realizar una prevención adecuada. El porcentaje de ictus isquémicos criptogénicos es demasiado elevado, y es preciso mejorar la detección de la FA. La isquemia cerebral cardioembólica por FA es prevenible, pero la inercia médica, la falta de adherencia del paciente y los problemas de los anticoagulantes orales antagonistas de la vitamina K hacen que muchos pacientes con FA estén en riesgo de sufrir una isquemia cerebral. Conclusiones: Los relevantes avances recientes con fármacos como la dronedarona y el dabigatrán abren una esperanza real para mejorar su prevención y pronto se reflejarán en las guías terapéuticas de prevención y, por lo tanto, los neurólogos debemos conocerlos. Keywords: Stroke, Atrial fibrillation, Prevention, Dronedarone, Dabigatran, Palabras clave: Ictus, Fibrilación auricular, Prevención, Dronedarona, Dabigatrán